2009
DOI: 10.1542/peds.2008-1597
|View full text |Cite
|
Sign up to set email alerts
|

Positive Association Between Attention-Deficit/ Hyperactivity Disorder Medication Use and Academic Achievement During Elementary School

Abstract: The finding of a positive association between medication use and standardized mathematics and reading test scores is important, given the high prevalence of attention-deficit/hyperactivity disorder and its association with low academic achievement. The 2.9-point mathematics and 5.4-point reading score differences are comparable with score gains of 0.19 and 0.29 school years, respectively, but these gains are insufficient to eliminate the test-score gap between children with attention-deficit/hyperactivity diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 26 publications
2
99
1
1
Order By: Relevance
“…This suggests that the association between ADHD medication use and the test scores after controlling for age and practice effects is relatively robust. Compared to many studies that used retrospective parental reports on medication use, 40 we inferred medication use during the test periods from medication prescription records. Thus, our results were not affected by any recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the association between ADHD medication use and the test scores after controlling for age and practice effects is relatively robust. Compared to many studies that used retrospective parental reports on medication use, 40 we inferred medication use during the test periods from medication prescription records. Thus, our results were not affected by any recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…In this study OROS MPH improved reading comprehension scores in comparison to placebo. Although the specific mechanisms associated with this improvement remain unknown, improved reading scores have also been documented in children with ADHD with extended use of MPH (Scheffler et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…They were also less likely to repeat a year in school. In terms of academic achievement, several studies have shown a positive relationship between duration of treatment and academic outcome [36][37][38]. Conversely, other reports have suggested that the dopaminergic effects of stimulants may alter the structure and function of the brain [39,40], and the long-term effects of this are unknown.…”
Section: Discussionmentioning
confidence: 99%